2021
DOI: 10.1155/2021/7742227
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Negative-Pressure Wound Therapy in Patients with Fracture-Related Infection: A Systematic Review and Critical Appraisal

Abstract: Introduction. Fracture-related infection (FRI) is a severe musculoskeletal complication in orthopedic trauma surgery, causing challenges in bony and soft tissue management. Currently, negative-pressure wound therapy (NPWT) is often used as temporary coverage for traumatic and surgical wounds, also in cases of FRI. However, controversy exists about the impact of NPWT on the outcome in FRI, specifically on infection recurrence. Therefore, this systematic review qualitatively assesses the literature on the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Recent studies have provided valuable insights and support for our research direction. For instance, Haidari et al's 36 study on the role of NPWT in fracture‐related infections underscores the challenges in managing soft tissue defects, similar to our study. However, our research provides more concrete evidence on the efficacy of combining NPWT with antibiotic‐loaded bone cement and flap coverage, highlighting a comprehensive approach towards traumatic osteomyelitis management.…”
Section: Discussionsupporting
confidence: 86%
“…Recent studies have provided valuable insights and support for our research direction. For instance, Haidari et al's 36 study on the role of NPWT in fracture‐related infections underscores the challenges in managing soft tissue defects, similar to our study. However, our research provides more concrete evidence on the efficacy of combining NPWT with antibiotic‐loaded bone cement and flap coverage, highlighting a comprehensive approach towards traumatic osteomyelitis management.…”
Section: Discussionsupporting
confidence: 86%
“…Regarding negative pressure therapy, a number of studies have shown a decreased infection rate in open tibial fractures, the possibility of extending the time to definitive coverage, and a lower failure rate of definitive flaps (63,64). However, other studies have shown no clear evidence for the advantage of this type of system over classic coverage (65,66,67,68). There are authors who value its use only temporarily until definitive coverage and no longer than 1 week due to the risk of colonisation with resistant microorganisms (69).…”
Section: Risk Factors and Preventionmentioning
confidence: 99%
“…The studies uncover the possible limitations of NPWT technology, but its advantages should not be fully denied. Regarding the role of NPWT in FRI therapy, a 2021 systematic review [ 104 ] indicated that there was still lack of strong evidence to support the use of NPWT as a definitive treatment for FRI. Similarly, in a recently published retrospective cohort study, Sweere et al [ 105 ] found that delayed wound closure with NPWT increased the risk of infection recurrence among patients with soft tissue defects following FRI treatment.…”
Section: Treatmentmentioning
confidence: 99%